Administrative Procedure: European Standards and Conclusions for Ukraine - BOIKO, Iryna V.; ZYMA, Oleksandr T.; MEKH, Yuliia V.; SOLOVIOVA, Olha M.; SOMINA, Valentyna A. (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019, 2019)
The relevance of the scientific article is due to the necessity to search for models of legal regulation of public relations that arise in public administration with a private person, which would meet the European standards of administrative procedure. The purpose of the article is to study the European experience of administrative and procedural ordering of public relations in order to form ideas of implementation in the legal field of Ukraine. The leading methods of research were the analysis of European practices of administrative procedure, modelling of legal structures acceptable to Ukraine. As a result of the research, proposals for legislative initiatives on the procedure for adopting administrative acts were formed. Research can be helpful to law-abiding lawyers and law enforcement officials, law school educators, and public administration officials and officials seeking to apply good administration standards and practices to individual management matters.